(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article expresses the views of our Prophet Muhammad (s.a.v) and the four holy chahariyors in the epic poem “Lisonu-t-tayr” by Alisher Navoi on the guardianship of Allah, their beautiful qualities characteristic of guardians and their revelations and revelations. The qualities that indicate their guardianship are explained in the stories in the epic.